Perencanaan Arsitektur Sistem Informasi Sekolah Menggunakan Metode TOGAF di SMK Guna Dharma Nusantara Cicalengka - Maulani, Anggi (Jurnal Dimamu, 2024)
The current bussiness processes at SMK Guna Dharma Nusantara have not fully integrated information systems. Although there has been progress in finacial management using a locally based system, most other activities are still coducted semi-manually at the school and utilize various applications. The aim of this research is to design an information system architecture for the school and recommend suitable applications. The Open Group Architecture Framework (TOGAF) method is used, starting from the Preliminary Phase, Requirement Management, Phase A: Architecture Vision, Phase B: Business Architecture, Phase C: Information Systems Architecture, Phase D: Technology Architecture, Phase E: Opportunities and Solutions, and Phase F: Migration Planning. This research will produce a blueprint for the school’s information system architecture that aligns with the school's objectives and recommend the development of 7 applications, which will be implemented gradually according to a predetermined schedule and timeline